Project Memory: A Flexible Access Approach For Contextual Knowledge Re-Use - Bekhti, Smain; Matta, Nada; Djaiz, Chaker (Journal of Knowledge Management Practice, 2009)
Knowledge sharing in general and contextual access to knowledge in particular, still represent a key challenge in knowledge management framework. Researchers on semantic web and human machine interface study techniques to enhance this access. For instance, in semantic web, the information retrieval is based on domain ontology. In human machine interface, keeping track of user's activity provides some elements of the context that can guide the access to information. We suggest an approach based on these two key guidelines, whilst avoiding some of their weaknesses. The approach permits a representation of both the context and the design rationale of a project for an efficient access to knowledge. In fact, the method consists of an information retrieval environment that, in the one hand, can infer knowledge, modeled as a semantic network, and on the other hand, is based on the context and the objectives of a specific activity (the design). The environment we defined can also be used to gather similar project elements in order to build classifications of tasks, problems, arguments, etc. produced in a company. These classifications can show the evolution of design strategies in the company.
Keywords: Project memory; Knowledge re-use; Knowledge representation; Conceptual graphs; Corese